Analysis 0f User Satisfaction With The Jconnect Mobile Application in Terms of Content, Accuracy, Format, Ease of Use, and Timeliness in Kediri City - Mahendra, Ihza Faisal; Fauji, Diah Ayu Septi (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This research aims to analyze user satisfaction with the JConnect Mobile application in terms of content, accuracy, format, ease of use, and timeliness in Kediri City. Methode: This study applies a quantitative methodology. The sampling technique utilizes a mixed sampling method. The sample consists of 60 users of the JConnect Mobile application. Data measurement in this research uses Statistical Package for the Social Sciences (SPSS) as the analytical tool. Research Finding: The t-test results reveal that the variables of content, accuracy, format, ease of use, and timeliness significantly affect purchasing decisions. Meanwhile, the F-test results show that price, content, accuracy, format, ease of use, and timeliness collectively significantly impact purchasing decisions. Theoretical contribution: This research provides a theoretical contribution by examining the impact of five dimensions of digital service quality (Content, Accuracy, Format, Ease of Use, and Timeliness) on user satisfaction within the context of the JConnect Mobile digital banking application. Contrasted to previous studies that primarily addressed the technical aspects of applications, this study adopts a managerial approach to analyze user experiences. Practitioner: This research recommends that Bank Jatim prioritizes improving Ease of Use as a primary factor of user satisfaction by developing an intuitive interface design and straightforward navigation. Furthermore, optimizing the dimensions of Content, Accuracy, Format, and Timeliness is crucial to strengthening digital service quality and advancing a more competitive digital banking transformation. Research limitation: This study is limited to a sample of 60 respondents and only covers the area of Kediri City, which means the findings cannot be widely generalized. Additionally, the research focuses only on five service quality dimensions without considering other factors that may also affect user satisfaction.